(untitled) (Research, Society and Development, 2024)
This case report describes a young adult woman who presented with spontaneous onset hypermenorrhea, with no previous clinical history. Laboratory tests confirmed the diagnosis of von Willebrand disease type 1, an inherited form of bleeding disorder characterized by a quantitative deficiency of von Willebrand factor. The diagnosis of von Willebrand disease type 1 is based on the evaluation of plasma levels of von Willebrand factor and platelet function tests, which reveal reduced levels of von Willebrand factor and decreased activity of von Willebrand factor in patients with this variant. Management of hypermenorrhea and other hemorrhagic manifestations is crucial. Treatment options include the use of combined oral contraceptives and tranexamic acid to regulate the menstrual cycle and reduce excessive bleeding during menstrual periods.